2020
DOI: 10.1002/eap.2114
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cetacean populations using integrated population models: an example with Cook Inlet beluga whales

Abstract: Effective conservation and management of animal populations requires knowledge of abundance and trends. For many species, these quantities are estimated using systematic visual surveys. Additional individual‐level data are available for some species. Integrated population modeling (IPM) offers a mechanism for leveraging these data sets into a single estimation framework. IPMs that incorporate both population‐ and individual‐level data have previously been developed for birds, but have rarely been applied to ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Whether the NMFS abundance trends reflect true changes in abundance or instead demonstrate how sensitive the methods used to estimate abundance are to changes in spatial distribution is unclear. An integrated population model, derived from the aerial survey data, hunt data, and our photo‐id data, had noted a change in group sizes detected during aerial surveys in 2010–2016, but concluded that it was uncertain whether the apparent decrease in group sizes was real or instead reflected a decrease in the proportion of groups counted by the survey (Jacobson et al, 2020). The contrast between our higher counts after 2010 and NMFS lower population estimates and smaller group sizes after that year are noteworthy and may suggest that temporal and spatial aggregation patterns have shifted in recent years.…”
Section: Discussionmentioning
confidence: 98%
“…Whether the NMFS abundance trends reflect true changes in abundance or instead demonstrate how sensitive the methods used to estimate abundance are to changes in spatial distribution is unclear. An integrated population model, derived from the aerial survey data, hunt data, and our photo‐id data, had noted a change in group sizes detected during aerial surveys in 2010–2016, but concluded that it was uncertain whether the apparent decrease in group sizes was real or instead reflected a decrease in the proportion of groups counted by the survey (Jacobson et al, 2020). The contrast between our higher counts after 2010 and NMFS lower population estimates and smaller group sizes after that year are noteworthy and may suggest that temporal and spatial aggregation patterns have shifted in recent years.…”
Section: Discussionmentioning
confidence: 98%
“…Realizing the diminished population status of CIB, Alaska Natives drastically reduced their hunting practices voluntarily between 2000 and 2004 through co-management agreements. The last CIB confirmed take by subsistence hunting was in 2005, with no co-management agreements being requested for CIB harvest since the end of the 2006 season (Huntington, 2000;NMFS, 2016;Jacobson et al, 2020). A "take" is defined by the U. S. Marine Mammal Protection Act as any action that seeks "to harass, hunt, capture, or kill or attempt to harass, hunt, capture, or kill any marine mammal" [16 U.S.C.…”
Section: Cook Inlet Beluga Whale Population Trendsmentioning
confidence: 99%
“…Integrated population models have been used extensively in fisheries (Wilberg et al 2005;Punt et al 2010;Brenden et al 2012;Goethel et al 2015;Jacobson et al 2020;Moremede et al 2020) and wildlife management (Rhodes et al 2011;Arnold et al 2018;Horne et al 2019;Messmer et al 2020). However, their use is typically FIGURE 8.…”
Section: Integrated Population Model With Batch-marking Datamentioning
confidence: 99%